LA SITUATION DE L'ENSEIGNEMENT DU FRANÇAIS AU SOUDAN (Bilan d'une expérience décevante) - Adam, Bachir Mohamed; Mohamed, Nadia Abdel Rahim (Journal of Faculty of Education, 2021)
Teaching French in Sudan has developed for over 04 years ago. It is the second European language after English to be the language of instruction until the arabization of the Sudanese educational system in 6522. This language is taught in schools, at universities and French institutes. In fact, the strategic location of Sudan between the Arab world and Africa besides its cultural richness would enable it to establish relations with francophone countries that favorite the teaching of French language. French language will not only enable to Sudan to consolidate its strategic position inside the African Francophone countries but also to promote the knowledge of the writers of the French language. This paper displays the situation of teaching French in Sudan by giving a brief historical background to French and English language teaching by presentation the principle establishments where French is taught, the conditions of teaching/learning and the characteristics of the Sudanese educational system. To give a clear picture of the situation of teaching this language, we presented the problems of teaching French at the Schools and universities. Observably, the conditions of French teaching at universities are more favored than its teaching in secondary schools. Despite the fact that the French plays an important role in communication, we find that Sudan hasn’t clear language planning for it. Consequently we present some suggestions that might in some way enhance the status of the French language in Sudan. For instance training teachers and adoption of program exchanges with French and Francophone universities to ensure good teaching situations is a case in point.